EFFICIENCY ANALYSIS OF ROTARY KILN EQUIPMENT IN FACTORY II PT. SEMEN BATURAJA (PERSERO) Tbk. REVIEW OF THERMAL EFFICIENCY - Perdana. Ts, Redho; Cundari, Lia; Safaruddin, Safaruddin; Robiansyah, Robiansyah (Jurnal Multidisipliner Bharasumba, 2022)
Semen Baturaja (Persero) Tbk. is a factory that produces cement as a raw material for construction for small to large scale. The cement industry is one of the industries that in the production process consumes a large amount of energy, the costs incurred for energy consumption in a cement factory range from 20% - 30% of the total cost of production. The largest energy requirement comes from the combustion process in the kiln. Rotary Kiln is the main equipment in the manufacture of cement which requires heat of combustion for the kilnker formation process. The main source of heat of combustion comes from coal. The evaluation of the rotary kiln was carried out to determine the performance of the calcination process on the rotary kiln which will affect the clinker formation in terms of processing time to the load on process costs. While the calculation method used by calculating the mass balance of each input and output component, as well as the heat balance of each input and output component. Then from the heat balance calculation can be used to calculate efficiency. From the calculation, the average actual efficiency is 60.33% with an average specific fuel consumption of 867.21 kcal/kg. The heat efficiency in the rotary kiln is not efficient because the efficiency of the rotary kiln is below the standard 80-85%.